Protein supplementation of ammoniated wheat straw: effect on intake and digestion in beef steers - Fike, G.D.; Simms, D.D.; Cochran, R.C.; Brandt, Robert T., Jr.; Vanzant, E.S.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixteen ruminally fistulated steers (avg wt. = 998 lb) were used in a 30-day conventional digestion trial to examine the effects of protein supplementation on intake and digestion of ammoniated wheat straw. Steers were assigned to one of four protein supplementation programs: 1) Control (C) - no supplement, 2) Low Protein (LP) - 4.5 lb of a 10% crude protein (CP) supplement, 3) Medium Protein (MP) - 4.5 lb of a 20% CP supplement, or 4) High Protein (HP) - 4.5 of a lb 30% CP supplement. Supplements were mixtures of milo and soybean meal. Supplementation increased (P<.05) dry matter intake, tended (P=.09) to increase intake of digestible neutral detergent fiber (NDF), and increased (P<.05) intake of forage dry matter. Dry matter digestibility was higher (P<.05) for HP steers than C and LP steers, but no difference was detected between MP, and HP steers. Steers on HP, MP, and C treatments exhibited higher NDF digestibility than LP steers. Rumen pH, total volatile fatty acid concentration, and acetate to propionate ratio were unaffected by supplementation.
Keywords: Beef; Ammoniation; Intake; Digestibility; Supplementation; Wheat straw